2014
DOI: 10.1021/jm500790x
|View full text |Cite
|
Sign up to set email alerts
|

Dualsteric Muscarinic Antagonists–Orthosteric Binding Pose Controls Allosteric Subtype Selectivity

Abstract: Bivalent ligands of G protein-coupled receptors have been shown to simultaneously either bind to two adjacent receptors or to bridge different parts of one receptor protein. Recently, we found that bivalent agonists of muscarinic receptors can simultaneously occupy both the orthosteric transmitter binding site and the allosteric vestibule of the receptor protein. Such dualsteric agonists display a certain extent of subtype selectivity, generate pathway-specific signaling, and in addition may allow for designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…Modes of a Dualsteric Agonist-Dualsteric (also termed bitopic orthosteric/allosteric) ligands (30) for muscarinic receptors are composed of orthosteric and allosteric moieties covalently connected via linkers of different chemical nature (31)(32)(33)(34). Recent studies suggested that at least some of these bipharmacophoric ligands may have more than one binding mode (28,34).…”
Section: Direct Pharmacological Evidence For Multiple Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Modes of a Dualsteric Agonist-Dualsteric (also termed bitopic orthosteric/allosteric) ligands (30) for muscarinic receptors are composed of orthosteric and allosteric moieties covalently connected via linkers of different chemical nature (31)(32)(33)(34). Recent studies suggested that at least some of these bipharmacophoric ligands may have more than one binding mode (28,34).…”
Section: Direct Pharmacological Evidence For Multiple Bindingmentioning
confidence: 99%
“…Unlike previous applications of gathering pharmacophore information from molecular dynamics (33,69), this new implementation works in a fully automated way: dynophore groups interaction points (such as hydrogen bonds, charges, and lipophilic contacts) of each trajectory frame according to their type and ligand atoms involved. All feature groups are graphically represented by three-dimensional volumetric feature density clouds, which are statistically characterized by occurrence frequency and interaction patterns with the protein.…”
Section: Site-directed Mutagenesis and Generation Of Stable Cellmentioning
confidence: 99%
“…Due to available crystal structures and mutational data, the M 2 receptor is a classical example in many studies 6e,11. The identified key residues for allosteric binding are Y177 and W422.…”
mentioning
confidence: 99%
“…Bitopic ligands, also described as ‘dualsteric’, bridge two different sites on a single GPCR, such as an orthosteric agonist site and an allosteric enhancer site [98,128]. A biotopic antagonist of the M 2 muscarinic receptor demonstrated that the orthosteric binding portion directs the allosteric moiety to establish its subtype selectivity [147]. …”
Section: New Pharmacological Dimensionsmentioning
confidence: 99%